Psychoanalysis vis-à-vis irony: A review of the main approaches and conceptions of irony - Gellis, Andre [UNESP]; Junta, Augusto Cesar [UNESP] (FapUNIFESP (SciELO), 2020)
Irony is a polymorphous notion, historically known for its polysemy and for posing an undeniable difficulty to its apprehension. This characteristic is redoubled in psychoanalysis, field in which the rare works dedicated to irony take one definition amongst many others. For Freud, irony is taken as a joke technique; for Reik, the rejection of a frustrating world; for Assoun, the rhetoric of Unconscious itself. This work aims to circumscribe the main approaches of irony, critically reviewing the specialized literature, highlighting the major questions and definitions of irony in order to provide elements to its approach in psychoanalysis.
A psicanálise vis-à-vis à ironia: Revisão das principais abordagens e concepções de ironia
Keywords: Irony; Lacan; Philosophy; Psychoanalysis; Theory of language